2012
DOI: 10.1177/1941738112454828
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Elbow Injuries in Youth Baseball Pitchers

Abstract: Context:Although baseball is a relatively safe sport, numerous reports suggest a rapid rise in elbow injury rate among youth baseball pitchers.Evidence Acquisition:PubMed was searched for epidemiologic, biomechanical, and clinical studies of elbow injuries in baseball (keywords: “youth OR adolescent” AND baseball AND pitching AND “ulnar collateral ligament OR elbow”; published January 2000 – April 2012). Studies with relevance to youth baseball pitchers were reviewed. Relevant references from these articles we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
183
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(186 citation statements)
references
References 36 publications
2
183
1
Order By: Relevance
“…Several reports have shown that these factors play a role in the incidence of elbow pain, elbow injury, and need for elbow surgery in youth and adolescent pitchers; it is possible that these unknown factors may have had an effect on our results. 16-18,33 Last, because our data were obtained from asymptomatic participants, it is difficult to say with certainty if these observed abnormalities on stress US correlate with clinical symptoms and instability. Despite this, our study has shown that stress US can be used for long-term surveillance of the elbows of elite-level pitchers.…”
Section: Discussionmentioning
confidence: 96%
“…Several reports have shown that these factors play a role in the incidence of elbow pain, elbow injury, and need for elbow surgery in youth and adolescent pitchers; it is possible that these unknown factors may have had an effect on our results. 16-18,33 Last, because our data were obtained from asymptomatic participants, it is difficult to say with certainty if these observed abnormalities on stress US correlate with clinical symptoms and instability. Despite this, our study has shown that stress US can be used for long-term surveillance of the elbows of elite-level pitchers.…”
Section: Discussionmentioning
confidence: 96%
“…39 Although research has long been directed at elucidating noncontact ACL injury mechanisms, the role of repetitive loading has received little attention. 33 Many joints in the human body are susceptible to repetitive loading injuries, including the wrist, 11 shoulder, 3 elbow, 10 intervertebral disc, 38 and hip. 5 In fact, failures due to tissue fatigue have been reported in the leporine medial collateral ligament 41 and the human extensor digitorum longus tendon.…”
mentioning
confidence: 99%
“…7 However, the incidence of Little League elbow, the most severe throwing injury among children, is increasing. 2 This injury can sometimes result in children no longer being able to play baseball; therefore, prevention is crucial for Little League baseball players. 4,5,9 …”
mentioning
confidence: 99%